IS RIGHT DONOR NEPHRECTOMY SAFE? OUR EXPERIENCE IN ARMED FORCES INSTITUTE OF UROLOGY - Khan, Haroon Sabir; Mahmood, Arshad; Bhatti, Ahsin Manzoor; Sabir, Sohail; Alvi, Sarwar; Kiani, Faaran (Pakistan Armed Forces Medical Journal, 2021)
Objective: To identify any adversities in the intraoperative and early postoperative outcome of right live-related donor nephrectomy.Study Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi, from Jan 2013 to Jul 2015.Methodology: A total of 143 successive patients underwent open live donor nephrectomies (right=41). Perioperative outcome for both sided procedures were analyzed to identify any difference as regard the intraoperative (warm ischemia time, total duration of surgery, peroperative complications) and early postoperative parameters (days of hospitalization, complications).Results: No statistically significant difference was found in studied parameters like total operative time, the warm ischemia time, duration of hospital stay and the intra- and early postoperative complications amongst both the groups. The mean warm ischemia time was 86 ± 12 seconds (Rt) versus 90 ± 12 seconds (Lt). The mean time for surgery was 110 ± 18.1 minutes (Rt) versus 121 ± 18.2 minutes (Lt). There were only five minor complications and one major complication.Conclusion: Right live-related donor nephrectomy is equally safe and feasible option with similar intra-and postoperative complications as for left side. Therefore, whenever required, it is safe to leave the donor with a better functioning kidney.